Transmission electron microscopy images of Cu₂Zn₁₋ₓMgₓSnS₄ nanoparticles - Boiko Bohdan; Yermakov Maksym; Vasyliev Vitalii; Pshenychnyi Roman; Diachenko Oleksii (DataverseUA, 2025)
Transmission electron microscopy images of Cu₂Zn₁₋ₓMgₓSnS₄ nanoparticles at x = (0.0, 0.2, 0.4, 0.6) with a 500 nm scale bar.